Analysis of the non-state medical services market in Ukraine - Prasol , Vladislav (Theory and Practice of Public Administration, 2019)
The introduction of market relations in social sphere is rather simple and scrupulous task, therefore, it requires the scientific substantiation of the peculiarities of management activity in the services market, especially medical ones.The medical system in Ukraine is represented by two sectors – state and private. Private medical services market in Ukraine is developing with mixed tendencies. Even in adverse times, the profitability of private health services is quite high. Unlike state-owned, private companies compete with each other, leads to a constant increase in internal efficiency and innovation. The main problem of the paid medical services development is the high level of initial investment in the opening of the clinic. Using new technologies (biotechnology), high-quality service, well-designed sites and the intensive use of advertising – all this allows us to predict the further active development of private medical institutions. In addition, the positive impact on the medical services market will also help to overcome the crisis in the economy in the country. In particular, the further development of the private sector of the Ukrainian healthcare market depends largely on the dynamics of population income growth.Significantly revive the healthcare market can successfully complete the medical reform launched in Ukraine. As a result, a competitive environment should be created in which both state and private medical institutions can develop harmoniously. Due to the principle of "money going for a patient", physicians will increase their interest in improving the quality of their work.